RIVALRY BETWEEN CHINA AND INDIA IN THE INDIAN OCEAN - Wulandari, Wahyu (Department of International Relations Universitas Satya Negara Indonesia, 2024)
The Indian Ocean plays an important role in the international world, especially for countries in the region. Starting from its strategic location and various advantages, the Indian Ocean has attracted the attention of many parties, especially those developing their respective interests. This article focuses on the rivalry between China and India in the Indian Ocean. The competition between the two has been going on for a very long time, starting from the division of territory to continuing to the Indian Ocean region. India considers itself the “owner of the Indian Ocean” and is disturbed by China’s activities. Both countries are trying to establish cooperation with several countries in the Indian Ocean region to gain strength in carrying out their interests. China considers the Indian Ocean great potential to increase its economic interests. Therefore, China is considered to be trying hard to develop its programs. From a realist perspective, this study sees that both countries act in the national interest and seek to maintain or increase their power in the international order. The researcher uses a qualitative method with descriptive analysis in this study. The data collection technique uses library research from various journals, articles, news, and theses whose contents are relevant to the topic of discussion. It was found that both countries depend on the Indian Ocean, where both have their economic interests. This then creates competition between the two which will certainly have an impact on surrounding countries, including countries that cooperate with China or India.